Óleo essencial de Dysphania ambrosioides extraído da inflorescência no controle de Botrytis cinerea em pós-colheita de Rosa hybrida - Salimena, Juliana Pace (2015)
Essential oils are natural complex substances biosynthesized by plants, with many presenting antimicrobial properties. Dysphania ambrosioides is a medicinal plant traditionally used as anthelmintic medication. In this study, the anti-fungal activity of the D. ambrosioides essential oil was tested against Botrytis cinerea, which is responsible for large economic losses in the postharvest of roses. D. ambrosioides inflorescences produced 1.3 mg.g-1 of essential oil, correspondent to 0.13%. Gas chromatography coupled to mass spectrometry (GC-MS) revealed 11 compounds in the essential oil, such as ascaridole and ocymene, correspondent to 80% of the total. The essential oil reduced mycelial growth of B. cinerea in 60% and spore germination in 51% at a concentration of 1000 ppm. However, we observed no apparent morphological alterations in scanning electron microscope. The essential oil was not capable of reducing mycelial growth on rose petals, however causing change in the color of the petals 24 hours after the treatment. Despite the essential oil presenting little potential in controlling B. cinerea on roses, due to the change in color it causes, its activity in mycelial growth and spore germination can by explored in other pathosystems.